The Effect of Fatigue and Job Stress on Turnover Intention with Emotional Intelligence as a Moderating Variable (A Case Study at the Bank Syariah Indonesia Office, Palu City) - Sakinah, Putri; Sari, Yoberth Kornelius; Sari, Wiri Wirastuti; Sari, Muh. Riswandi Palawa (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of job fatigue and job stress on turnover intention, with emotional intelligence as a moderating variable among employees of Bank Syariah Indonesia in Palu City. This associative quantitative study used primary data from 54 respondents analyzed using SEM-PLS. The results show that job fatigue and job stress have a significant positive effect on turnover intention. Emotional intelligence significantly moderates this relationship, strengthening the effect of fatigue but weakening job stress. Consequently, improving emotional intelligence is crucial for suppressing turnover intention and improving human resource stability in the banking sector. Keywords: Burnout; Work Stress; Turnover Intention; Emotional Intelligence